2022
DOI: 10.1182/blood.2021011532
|View full text |Cite
|
Sign up to set email alerts
|

Systemic IL-15 promotes allogeneic cell rejection in patients treated with natural killer cell adoptive therapy

Abstract: NK cells are a promising alternative to T cells for cancer immunotherapy. Adoptive therapies with allogeneic, cytokine-activated NK cells are being investigated in clinical trials. However, the optimal cytokine support after adoptive transfer to promote NK cell expansion, and persistence remains unclear. Correlative studies from two independent clinical trial cohorts treated with MHC-haploidentical NK cell therapy for relapsed/refractory AML revealed that cytokine support by systemic IL-15 (N-803) resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Of note, adoptive transfer of IL-12/15/18-preactivated NK cells is usually followed by the administration of IL-15 or IL-2 to support their survival and expansion, although cytokine support requires further characterization. Recent findings suggested that the infusion of IL-15 superagonist N-803 following adoptive CIML NK cell transfer may limit their clinical activity in comparison with IL-2 infusions ( 76 ). Remarkably, CAR-NK cells can be further modified to express and secrete cytokines such as IL-15 ( 77 82 ), so it would be interesting to explore if a therapy based on CAR-engineered CIML NK cells expressing IL-15 or IL-2 could further improve their efficacy.…”
Section: Cytokine-induced Memory-like (Ciml) Nk Cellsmentioning
confidence: 99%
“…Of note, adoptive transfer of IL-12/15/18-preactivated NK cells is usually followed by the administration of IL-15 or IL-2 to support their survival and expansion, although cytokine support requires further characterization. Recent findings suggested that the infusion of IL-15 superagonist N-803 following adoptive CIML NK cell transfer may limit their clinical activity in comparison with IL-2 infusions ( 76 ). Remarkably, CAR-NK cells can be further modified to express and secrete cytokines such as IL-15 ( 77 82 ), so it would be interesting to explore if a therapy based on CAR-engineered CIML NK cells expressing IL-15 or IL-2 could further improve their efficacy.…”
Section: Cytokine-induced Memory-like (Ciml) Nk Cellsmentioning
confidence: 99%
“…Exogenous cytokine support has been proposed to lengthen NK therapy persistence. Nevertheless, the IL-15 superagonist complex N-803 reduces clinical responses in AML patients treated with haploidentical ML-NK cells because of CD8 + T lymphocytes stimulation (NCT03050216 and NCT01898793) ( 136 ). Alternatively, autocrine secretion from bicistronic CAR constructs containing cytokines may provide a better approach.…”
Section: Manufacturing Conditions: Key Aspect For the Efficacy Of Car...mentioning
confidence: 99%
“…N-803 has been used instead of IL-2 to support cytokine-primed allogeneic NK cells transfer to AML patients in a relapse in two separate clinical trials (NCT03050216 and NCT01898793). Unexpectedly, the report stated that the use of N-803 instead of IL-2 led to reduced clinical activity (93). The authors showed that N-803 promotes recipient CD8+ T-cell activation, inducing a decrease in allogeneic NK cell persistence through rejection.…”
Section: Cytokine Primingmentioning
confidence: 99%